Dengue virus surveillance: Detection of DENV-4 in the city of Sao Jose do Rio Preto, SP, Brazil - Colombo, Tatiana Elias; Vedovello, Danila; Pacca-Mazaro, Carolina Colombelli; Mondini, Adriano; Araujo, Joao Pessoa [UNESP]; Cabrera, Eliana; Lopes, Jose Carlos; Penha dos Santos, Izalco Nuremberg; Negri Reis, Andreia Francesli; Costa, Fabiana Rodrigues; Arao Antonio Cruz, Lilian Elisa; Ferreira, Jurandir; et al. (Elsevier B.V., 2016)
Dengue viruses are the most common arbovirus infection worldwide and are caused by four distinct serotypes of the dengue virus (DENV). In the present study, we assessed DENV transmission in Sao Jose do Rio Preto (SJRP) from 2010 to 2014. We analyzed blood samples from febrile patients who were attended at health care centers in SJRP. DENV detection was performed using multiplex RT-PCR, using flavivirus generic primers, based on the genes of the non-structural protein (NS5), followed by nestedPCR assay with species-specific primers. We analyzed 1549 samples, of which 1389 were positive for NS1 by rapid test. One thousand and eight-seven samples (78%) were confirmed as positive by multiplex RTPCR: DENV-4, 48.5% (528/1087); DENV-1, 41.5% (449/1087); DENV-2, 9.5% (104/1087); and co-infection (5 DENV-1/DENV-4, 1 DENV-1/DENV-2), 0.5% (6/1087). Phylogenetic analysis of the DENV-4 grouped the isolates identified in this study with the American genotype and the showed a relationship between isolates from SJRP and isolates from the northern region of South America. Taken together, our data shows the detection and emergence of new dengue genotype in a new region and reiterate the importance of surveillance programs to detect and trace the evolution of DENV. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dengue virus; Transmission; Phylogenetic analysis; Surveillance programs